Танцы с Варежкой: роман / Е. Н. Вильмонт - Вильмонт Екатерина Николаевна (Астрель, 2012)
Экземпляры: аб. Камская библиотека (20210317) / Инвентарный номер: 9491 / Цена: / Авт.знак: В 46 / ББК: 84(2Рос-Рус)6-44